Dampak Revolusi Industri 4.0 Terhadap Kesiapan Indonesia - Rendra Kurniawan; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The industrial revolution has transformed the global economic landscape, and Indonesia is not exempt from its impacts. This article discusses Indonesia's readiness to face the challenges posed by the industrial revolution, focusing on sectors such as manufacturing, technology, and human resources. This research is a qualitative analysis method with a literature study and interviews approach. The findings indicate that while Indonesia has made progress in infrastructure and technology, there are still significant challenges in terms of human resource quality and the industry's readiness to adapt to technological advancements. Therefore, more targeted policies are needed to optimize Indonesia's potential in facing the industrial revolution.